Dampak Banjir Bagi Masyarakat Di Nagari Sungai Buluh Barat Kecamatan Batang Anai Kabupaten Padang Pariaman - Darma Nabila, Rizka; Rianto, Slamet; Despica, Rika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the flood disaster that occurred in Sungai Buluh Barat Village, Batang Anai District, Padang Pariaman Regency, which significantly affected the social and economic conditions of the community. The study aimed to analyze the classification of flood damage and its impacts on the community's social and economic conditions. A mixed methods approach was employed by combining quantitative and qualitative methods. Informants were selected using purposive sampling and consisted of the Village Head, hamlet heads, and flood-affected residents. Data were collected through observation, interviews, and documentation. Qualitative data were analyzed using NVivo 15, while spatial analysis was applied to classify the level of flood damage.The results showed that flood damage was classified into three categories: minor, moderate, and severe, across seven affected hamlets involving 1,133 households. The social impacts included disrupted social interactions, psychological trauma, displacement, and increased health problems caused by poor environmental sanitation. The economic impacts included crop failure, temporary unemployment, infrastructure damage, and disruption of economic activities, resulting in decreased community income. The findings are expected to serve as a reference for the government and the community in strengthening flood mitigation and disaster management efforts.